Fcast Multicast File Distribution - Gemmell, Jim; Schooler, Eve; Gray, Jim (Institute of Electrical and Electronics Engineers, Inc., 2000)
Reliable data multicast is problematic. ACK/NACK schemes do not scale to large audiences, and simple data replication wastes network bandwidth. Fcast, “file multicasting”, combines multicast with Forward Error Correction (FEC) to address both these problems. Like classic multicast, Fcast scales to large audiences, and like other FEC schemes, it uses bandwidth very efficiently. Some of the benefits of this combination were known previously, but Fcast contributes new caching methods that improve disk throughput, and new optimizations for small file transfers. This paper describes Fcast's design, implementation, and API.